STUDY OF CYCLICITY AND MACROECONOMIC IMPACT ON INVEST- MENT FLOWS IN EAST JAVA - Ariz Aprilia; Nofita Wulansari (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2017)
This paper aims to analysis the cyclicity pattern and to estimates the effect of macroeconomics indicators on capital inflows in East Java. The first analysis by using Hodrick-Prescott (HP) filter shows that capital inflows in East Java have a tendency to move in procyclical pattern. While the second by using VAR analysis shows that macroeconomics indicators are dominant factor for investors to invest their funds in East Java. Likewise, this paper indicates the pattern of capital inflows in East Java is tend to procyclical. Moreover,the macroeconomics indicators that affect capital inflows in East Java are economic growth and inflation. Based on the result, this paper suggest for local governments to synchronize the development of capital inflows together with macroeconomics conditions. Furthermore, the capital inflows can be managed properly to avoid the “surges” and “sudden stop” phenomenon.